Menumbuhkan motivasi belajar perspektif Hadits Sunan Ibnu Majah - Yana, Virda; Dani, Mulia; Purnomo, Eko (Tawazun: Jurnal Pendidikan Islam, 2022)
Learning is a process of becoming better and leading to positive change. Learning motivation is the spirit possessed by an individual both within himself and from outside. Motivation is the driving force that encourages students to continue to actively learn in order to achieve the desired goals. The research method used is a library research approach. The primary sources in this study are the hadith about motivation from Sunan ibn Majah and several other hadiths about learning motivation as well as several journal articles related to learning motivation as secondary sources. The data analysis technique uses content analysis. In many hadiths it is explained about the motivation to learn, one of which is "Whoever takes the road in order to seek knowledge, then Allah makes the path to heaven easy". From these hadith quotes, it can provide its own motivation for people who understand and carry out sincerely and enthusiastically in studying. In the hadith of Sunan ibn Majah there is also a hadith that explains that angels will shorten their wings to protect those who seek knowledge, even the residents of the sky to the fish in the sea also ask forgiveness for those who seek knowledge. From the two hadiths, it has shown the magnitude of the fadolence that Allah has given to people who seek knowledge and should be a motivation for all of us to be enthusiastic in studying. Abstrak Belajar merupakan sebuah proses menjadi lebih baik dan menuju perubahan yang positif. Motivasi belajar adalah semangat yang dimiliki seorang individu baik dalam dirinya sendiri maupun dari luar. Motivasi menjadi dasar penggerak yang mendorong peserta didik terus bergerak aktif belajar agar bisa mencapai tujuan yang diinginkan. Metode penelitian yang digunakan adalah pendekatan kepustakaan (library research). Sumber primer dalam penelitian ini adalah hadis tentang motivasi dari sunan ibnu majah dan beberapa hadis lain tentang motivasi belajar serta beberapa artikel jurnal yang berkaitan dengan motivasi belajar sebagai sumber sekunder. Teknik analisis data menggunakan analisis isi (content analysis). Dalam hadist banyak dijelaskan tentang motivasi belajar salah satunya adalah "Barang siapa yang menempuh jalan dalam rangka menuntut ilmu pengetahuan, maka Allah mudahkan jalan menuju syurganya”. Dari kutipan hadist tersebut dapat memberikan motivasi tersendiri bagi orang yang memahami dan menjalankan dengan tulus dan semangat dalam menuntut ilmu. Dalam hadis sunan ibnu majah juga terdapat hadis yang menjelaskan bahwasannya malaikat akan memendekkan sayapnya untuk menaugi kepada orang yang menuntut ilmu, bahkan penduduk langi sampai dengan ikan yang ada dilaut juga memintakan ampun bagi orang yang menuntut ilmu. Dari kedua hadis tersebut sudah menunjukan besarnya kefadolan yang diberikan Allah kepada orang yang menuntut ilmu dan seharusnya menjadi motivasi bagi kita semua untuk semangat dalam menuntut ilmu.